Improving The Student’s Pronunciation Skill Trough Choral Drill Technicqu And Shadow Practice - Ade Irma (Journal of Research Education and English Teaching, 2025)
This is a mini research. The study of the research is about the effectiveness of using choral drill method and shadow as a medium to improving students pronunciation . the background of the study is the difficulties in learning pronunciation. This study is aimed at responding the following question : (1) how is the implementation of choral drill to improve pronunciation? (2) how is the effectiveness of choral drill method and shadow practice in learning pronunciation?. The population of this research are science major of the first grade Islamic High School One Majene who consist of 30 students. This is a small research. The method of data collection is test. There are two test; pre and post test which both are in the form of reading aloud test while practicing choral drill method. intended to find out how pronunciation instruction was handled in the language classroom with Islamic High School students and also understand if pronunciation instruction had an impact on students' confidence when using English. In order to do this, a qualitative case study was carried out with learners of Class observation, a written text, and semi-structured interviews comprised the data collection instruments. The findings showed that not only teacher pronunciation instruction is necessary when learning English as a foreign language but that a lot of student practice is key to developing and enhancing learners' pronunciation as well. The aim of this research is to solve the English pronunciation problem. Besides, this research is also to know the effectiveness of using choral drill technique in teaching pronunciation. The research is conducted at Islamic High School One Majene. Data needed is obtain from direct and indirect observation and collaboration. In the direct observation, the data is from field observation. In the indirect one, the data is from the test result. Meanwhile in collaboration, the collaborator informs teaching and learning process through choral drill technique . Based on the data collected it is found that some students are active in pronunciation practice through choral drill technique and shadow practice. Further, the students have more desire and motivation to improve their pronunciation skill.